The fauna and summer population of birds of the Uysky natural biological reserve (Chelyabinsk region) - V.A. Gashek; V.D. Zakharov; B.V. Krasutsky; D.A. Yasko (Трансформация экосистем)
Based on the results of ornithological studies conducted in the Uysky Nature Biological Reserve in 1986, 1987, 2005, 2018 and 2023, an annotated list of bird species was compiled. The presence of 146 species was identified, of which 129 nest (or nesting is assumed) on its territory and In the immediate vicinity. According to the averaged data of quantitative censuses (1986–1987), the dominant forest bird species in terms of numbers were the Chaffinch (21% of the population), the Willow Tit and the Tree Pipit (15% each). In 2018 and 2023, the most numerous were the Chaffinch, Tree Pipit, Great Tit, Common Chiffchaff and the Willow Tit. The Great Grey Owl was found quite common (0.3 individuals/km2). Changes in the species composition and relative abundance of most bird species in the Uysky pine forest from the 1980s to the 2020s were very insignificant. In recent years, Mute and Whooper Swans have appeared in the nesting fauna. In the open habitats of the reserve, which are fields of agricultural crops and heavily degraded pastures, in 2023, extremely poor species diversity of nesting species and low numbers of most bird species were observed. The drying up of small ponds and strong shallowing of larger ones caused a very noticeable decrease in the diversity (by more than 20%) and abundance of nesting waterfowl and near-water species. A negative impact of illegal logging and disturbance during the nesting period on the nesting group of the Imperial Eagle was revealed.